CASE BASED REASONING UNTUK PENENTUAN JENIS BEASISWA INTERNAL (BSM DAN PPS) UNIVERSITAS ‘AISYIYAH YOGYAKARTA - Esi Putri Silmina (LPPM STMIK El Rahma Yogyakarta, 2018)
Education is the most important thing to educate the nation's life, but there are still many students who fail because of constrained tuition fees, in order to overcome this, the University of 'Aisyiyah Yogyakarta provides internal scholarship assistance to students in the form of Student Study Assistance (BSM) scholarships and Scholarship Improvement Scholarships (PPS). Many students apply for scholarships each year. The criteria for submitting scholarships tend to be similar every year, resulting in data being used to assess repetitions or having similarities between old data and new data. Case Based Reasoning (CBR) is a system that aims to solve a new case by adapting solutions found in previous similar cases. To simplify the process of determining the type of scholarship obtained by students, Case Based Reasoning is used. Similarity calculation for the case of determining the type of PPS and BSM scholarship using Euclidean Distance Similarity. The results of the K05 case similarity calculation are similar to the K02 case, the similarity value obtained is 0.86727, so the K05 case will get a PPS scholarship